Review Paper Data Mining Klasifikasi Data Mining - Srirahayu, Agustina; Pribadie, Laras Setya (Jurnal Ilmiah Informatika Global, 2023)
The process of combining statistical techniques, mathematical calculations, Artificial Intelligence (AI) and machine learning to extract useful and interrelated information from large amounts of data. Data mining is commonly used to analyze and explore big data to get useful information. There is a lot of information that can be extracted from processing using data mining, such as analyzing consumer purchases or making decisions regarding the production process. Science has often been implemented to solve problems that arise from existing circumstances. In addition to the knowledge needed in order to solve problems or make strategic decisions in dealing with problems that arise, past experience or data that has been obtained at the time of the lights can also be used as a reference for making decisions. Data mining is the process of extracting (mining) information from a set of past data which is then displayed as knowledge to be used in accordance with the desired needs. Research on data mining has been carried out by many researchers to date related to the application of data mining to solve the problems they face, even though the problems are different in type and designation. This paper was written to review existing papers regarding data mining, especially classification. And to get information and map from research that has been done to be used as literature on the author's research plan. Through this review, it is hoped that later you can choose the right method to process data using data mining for the best results.